Effects of signal seeding on long-wavelength-band Er3+-doped fiber amplifiers - Mahdi, M.A.; Adikan, Faisal Rafiq Mahamd; Poopalan, P.; Selvakennedy, S.; Ahmad, Harith (International Society for Optical Engineering (SPIE), 2001)
A study of gain improvement in the long-wavelength band (L-band) by a seeding signal from the conventional-wavelength band (C-band) is presented. The seeding signal reduces losses through amplified spontaneous emission and supplies energy for L-band amplification in the underpumped region. Gain improvement is observed for a copumped configuration, where the L-band and seeding signal are colaunched together with minimal noise figure penalty when an optimized seeding signal is used. The seeding signal boosts the L-band gain profile in the underpumped region to the flat-gain profile with gain flatness of less than 1 dB. High flat-gain values of 24 dB with gain variation of less than 0.9 dB when a seeding signal at 1555 nm is applied to the L-band amplifier pumped by only 105 mW from a 980 nm pump laser, A gain improvement of 52 dB is obtained at 1580 nm with this architecture. (C) 2001 Society of Photo-Optical Instrumentation Engineers.